2019
DOI: 10.1088/1361-6560/ab12f2
|View full text |Cite
|
Sign up to set email alerts
|

Ionization quenching in scintillators used for dosimetry of mixed particle fields

Abstract: Ionization quenching in ion beam dosimetry is often related to the fluence-or dose-averaged linear energy transfer (LET). Both quantities are however averaged over a wide LET range and a mixed field of primary and secondary ions. We propose a novel method to correct the quenched luminescence in scintillators exposed to ion beams. The method uses the energy spectrum of the primaries and accounts for the varying quenched luminescence in heavy, secondary ion tracks through amorphous track structure theory. The ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 28 publications
2
10
0
Order By: Relevance
“…Such an analysis had not been done for BaFBr 0.85 I 0.15 :Eu 2+ dosimeters but it is also likely that they will lead to similar findings given the related PSL mechanisms of the two inorganic dosimeters. However, we have since noted a successful application of a more fundamental and quantitative alternative to the cylindrical infratrack theory by Christensen et al to organic plastic scintillators 48 and for our future work, we will be investigating the theoretically predicted quenching magnitudes of BaFBr 0.85 I 0.15 :Eu 2+ dosimeters using this more fundamental approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such an analysis had not been done for BaFBr 0.85 I 0.15 :Eu 2+ dosimeters but it is also likely that they will lead to similar findings given the related PSL mechanisms of the two inorganic dosimeters. However, we have since noted a successful application of a more fundamental and quantitative alternative to the cylindrical infratrack theory by Christensen et al to organic plastic scintillators 48 and for our future work, we will be investigating the theoretically predicted quenching magnitudes of BaFBr 0.85 I 0.15 :Eu 2+ dosimeters using this more fundamental approach.…”
Section: Discussionmentioning
confidence: 99%
“…41 Their applicability in describing physical effects such as the experimental under-responses is a choice that seems to be detector dependent. For instance, Christensen et al, had shown that track-averaged LET values were more accurate in predicting the magnitude of proton quenching of plastic scintillators 48 whereas other authors have shown that dose-averaging was a more accurate measure for other dosimeters such as OSLDs 25 and radiochromic films. 26,49 As such, it is important for us to determine the more accurate averaging scheme (dose-or track-averaging) that is more relevant to BaFBr 0.85 I 0.15 :Eu 2+ dosimeters.…”
Section: G Analytical Proton Stopping Power Ratio and Experimentalmentioning
confidence: 99%
“…The OSLDs are omitted from the simulations for two reasons. Firstly, since a study 9 showed that the signal averaging over 1 mm wide plastic detectors was in proton beams, the signal averaging over the powder layer is expected to be negligible. Secondly, the OSLDs are calibrated in terms of dose and LET in water.…”
Section: Methodsmentioning
confidence: 99%
“…Ionization quenching is occasionally exploited to estimate the LET by comparing the response of two detectors having different quenching characteristics, e.g. scintillators relative to absorbed dose calorimeters 8 or scintillators relative to ionization chambers 9 . Similarly, pairs of differently quenching organic scintillators 10 , thermoluminescent detectors 11 or phosphor films 12 have been used to simultaneously estimate dose and LET, which, however, is associated with large uncertainties in regions with steep gradients, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…(1) . Following Christensen et al [30] , the LET d values included in the model were scored from the entrance to the 80% distal dose point.…”
Section: Methodsmentioning
confidence: 99%